2021
DOI: 10.1073/pnas.2106478118
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire smoke impacts on indoor air quality assessed using crowdsourced data in California

Abstract: Wildfires have become an important source of particulate matter (PM2.5 < 2.5-µm diameter), leading to unhealthy air quality index occurrences in the western United States. Since people mainly shelter indoors during wildfire smoke events, the infiltration of wildfire PM2.5 into indoor environments is a key determinant of human exposure and is potentially controllable with appropriate awareness, infrastructure investment, and public education. Using time-resolved observations outside and inside more than 1,40… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 42 publications
7
86
1
Order By: Relevance
“…A study of 1400 buildings taken from the PurpleAir sensor network in two California areas during times of wildfires calculated infiltration ratios for days influenced or not influenced by fires [ 37 ]. The ratios were lower during wildfire days indicating that residents took action to protect themselves from the worsened outdoor air.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 1400 buildings taken from the PurpleAir sensor network in two California areas during times of wildfires calculated infiltration ratios for days influenced or not influenced by fires [ 37 ]. The ratios were lower during wildfire days indicating that residents took action to protect themselves from the worsened outdoor air.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have not attempted to incorporate a correction for RH. Another recent study of 1400 PurpleAir monitors in northern and southern California at times of wildfires found the RH effect was too small to include in their model [12].…”
Section: Limitationsmentioning
confidence: 99%
“…Published calibration factors based on the Plantower CF_1 algorithm, such as the value of 0.53 [12] and the EPA value of 0.54 [11], all indicate that the CF_1 algorithm overestimates PM 2.5 concentrations, perhaps by nearly a factor of 2. Similarly, the ALT-CF3 algorithm, which is not based on CF_1, is 0.55 times CF_1.…”
Section: Comparison With Other Algorithms and Effect On The Aqimentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies on particulate-bound PAHs have found different results, wherein outdoor air concentrations were consistently higher than indoor air concentrations. 65 67 Since PAHs can be present in both the vapor phase and particulate phase, 19 and vapor-phase PAHs can account for up to 86% of the cancer risk from total inhalation exposure (vapor phase and particulate matter), 20 23 our results provide an important consideration for public health recommendations during wildfire events.…”
Section: Resultsmentioning
confidence: 78%